Modelling the Modes of System of Asynchronous Centrifugal Units of Multi-Unit Pumping Station with Serial Connection of Pumps - Vladyslav Lysiak; Mykhailo Oliinyk (Energy Engineering and Control Systems)
Based on the current regulations on pipeline transport, the need for a systematic approach to the study of processes occurring in the technological complexes of pumping stations of the main pipelines and their power supply systems is shown. The development of effective control systems for such complexes in order to reduce energy consumption involves a comprehensive analysis of current modes and forecasting of both steady-state and dynamic modes by simultaneously studying their subsystems as a whole The replacement of obsolete centrifugal pumps of multi-unit pumping stations with main and booster pumps with the modern types with a significantly higher efficiency increases the importance of energy saving potential in dynamic modes. The scientific research results regarding modelling of pumping stations and their electrical complexes are analysed. It is shown that the generally accepted approach is not always sufficient for the effective study of the influence of subsystems of different physical nature of pumping stations on the power supply system and the mutual influence of these subsystems on each other. A formalized mathematical model of the system of asynchronous centrifugal units of a multi-unit pumping station with serial connection of pumps is built, its verification is carried out and the prospects of its use are discussed.